Reliable data storage system design and implementation for acoustic logging while drilling. (28th November 2016) - Hao, Xiaolong; Ju, Xiaodong; Wu, Xiling; Lu, Junqiang; Men, Baiyong; Yao, Yongchao; Liu, Dong
Abstract: Owing to the limitations of real-time transmission, reliable downhole data storage and fast ground reading have become key technologies in developing tools for acoustic logging while drilling (LWD). In order to improve the reliability of the downhole storage system in conditions of high temperature, intensive shake and periodic power supply, improvements were made in terms of hardware and software. In hardware, we integrated the storage system and data acquisition control module into one circuit board, to reduce the complexity of the storage process, by adopting the controller combination of digital signal processor and field programmable gate array. In software, we developed a systematic management strategy for reliable storage. Multiple-backup independent storage was employed to increase the data redundancy. A traditional error checking and correction (ECC) algorithm was improved and we embedded the calculated ECC code into all management data and waveform data. A real-time storage algorithm for arbitrary length data was designed to actively preserve the storage scene and ensure the independence of the stored data. The recovery procedure of management data was optimized to realize reliable self-recovery. A new bad block management idea of static block replacement and dynamic page mark was proposed to make the period of data acquisition and storage more balanced. In addition, we developed a portable ground data reading module based on a new reliable high speed bus to Ethernet interface to achieve fast reading of the logging data. Experiments have shown that this system can work stably below 155 °C with a periodic power supply. The effective ground data reading rate reaches 1.375 Mbps with 99.7% one-time success rate at room temperature. This work has high practical application significance in improving the reliability and field efficiency of acoustic LWD tools.